Serum Bilirubin and 6-min Walk Distance as Prognostic Predictors for Inoperable Chronic Thromboembolic Pulmonary Hypertension: A Prospective Cohort Study - Juan-Ni Gong (Chinese Medical Journal, 2015)
Background: Inoperable chronic thromboembolic pulmonary hypertension (CTEPH) is a severe clinical syndrome characterized by right cardiac failure and possibly subsequent liver dysfunction. However, whether serum markers of liver dysfunction can predict prognosis in inoperable CTEPH patients has not been determined. Our study aimed to evaluate the potential role of liver function markers (such as serum levels of transaminase, bilirubin, and gamma-glutamyl transpeptidase [GGT]) combined with 6-min walk test in the prediction of prognosis in patients with inoperable CTEPH. Methods: From June 2005 to May 2013, 77 consecutive patients with inoperable CTEPH without confounding co-morbidities were recruited for this prospective cohort study. Baseline clinical characteristics and 6-min walk distance (6MWD) results were collected. Serum biomarkers of liver function, including levels of aspartate aminotransferase, alanine aminotransferase, GGT, uric acid, and serum bilirubin, were also determined at enrollment. All-cause mortality was recorded during the follow-up period. Results: During the follow-up, 22 patients (29%) died. Cox regression analyses demonstrated that increased serum concentration of total bilirubin (hazard ratio [HR] = 7.755, P < 0.001), elevated N-terminal of the prohormone brain natriuretic peptide (HR = 1.001, P = 0.001), decreased 6MWD (HR = 0.990, P < 0.001), increased central venous pressure (HR = 1.074, P = 0.040), and higher pulmonary vascular resistance (HR = 1.001, P = 0.018) were associated with an increased risk of mortality. Serum concentrations of total bilirubin (HR = 4.755, P = 0.007) and 6MWD (HR = 0.994, P = 0.017) were independent prognostic predictors for CTEPH patients. Patients with hyperbilirubinemia (≥23.7 μmol/L) had markedly worse survival than those with normobilirubinemia. Conclusion: Elevated serum bilirubin and decreased 6MWD are potential predictors for poor prognosis in inoperable CTEPH.